Portable meters for nutritional assessment in plants of gerbera fertigated with electrical conductivity levels - Poliana R. D'A. Mota; Roberto L. Villas Bôas; Fernanda Ludwig; Dirceu M. Fernandes; Marcos V. Folegatti (Revista Brasileira de Engenharia Agrícola e Ambiental)
Rapid tests to assess the nutritional status of plants gerbera can make easier the decision of any adjustments in the fertilization of the substrate. The study was conducted to evaluate nutritionally fertigated gerbera plants with increasing levels of electrical conductivity (EC), using portable meters nitrate and potassium, and chlorophyll. For this, two experiments were conducted. A randomized block design with five levels of EC (0.5, 2.0, 3.5, 5.0 and 6.5 dS m-1) and four replications was used. Cherry cultivar was used in the first experiment. In the second experiment, two cultivars (Cherry and Salmon Rose) were used. In the first experiment, the sap of the leaves was subjected to rapid testing of N-NO3- (equipment Cardy Horiba C -141). N-NO3- and K+ (C-131) were determined in the substrate solution. The intensity of the green leaf, in the second experiment was evaluated with portable Chlorophyll Meter. The N content in the indicator leaf in the first and N and K contents in the plant in the second experiment were determined. Rapid tests are presented as good indicators of the level of N-NO3- and K+ in plant tissue, with the advantages of convenience and speed of determination, facilitating monitoring of fertilization of the substrate by producers and technicians.